The Use of Three-Dimensional Documentation Technologies in Archaeological Applications ... - Jahraus, Adam (Graduate Studies, 2017)
In archaeology, it is useful to document the shape of features of interest. There are many three-dimensional measurement technologies available that can help accomplish this task. An error model for a handheld 3D scanner called the DPI-7 was created. This error model reduced the errors in the in-plane directions by up to 59%. The levels of precision in two technologies, terrestrial laser scanning and computer vision assisted photogrammetry, were determined through the simulation of observations in a virtual environment. It was found that terrestrial laser scanning point observations had a standard deviation (in the direction of least precision) of 6mm, while photogrammetry could achieve a value of 10mm. The point cloud data from the scans of an excavation in the Canadian arctic were used to create a detailed and coloured visual model of the site, and was subsequently used in a virtual reality visualization of the site in question. ...